2001
DOI: 10.1523/jneurosci.21-24-09917.2001
|View full text |Cite
|
Sign up to set email alerts
|

Control of Dorsal Raphe Serotonergic Neurons by the Medial Prefrontal Cortex: Involvement of Serotonin-1A, GABAA, and Glutamate Receptors

Abstract: Anatomical evidence indicates that medial prefrontal cortex (mPFC) neurons project to the dorsal raphe nucleus (DR). In this study, we functionally characterized this descending pathway in rat brain. Projection neurons in the mPFC were identified by antidromic stimulation from the DR. Electrical stimulation of the mPFC mainly inhibited the activity of DR 5-HT neurons (55 of 66). Peristimulus time histograms showed a silence of 150 +/- 9 msec poststimulus (latency, 36 +/- 1 msec). The administration of WAY-1006… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

31
384
1
6

Year Published

2003
2003
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 470 publications
(422 citation statements)
references
References 64 publications
31
384
1
6
Order By: Relevance
“…Thus, in line with previous reports (Moghaddam et al, 1997;Adams and Moghadam, 2001;Lorrain et al, 2003), MK-801 increases glutamate release onto AMPA/kainate receptors, which, in turn, elicit an enhanced glutamatergic output from mPFC neurons, including those projecting to the dorsal raphe nucleus, thereby increasing serotonergic cell firing and cortical 5-HT efflux. Although this functional interplay between the mPFC and the dorsal raphe nucleus is well documented (Hajós et al, 1998;Celada et al, 2001;Martín-Ruiz et al, 2001;Amargós-Bosch et al, 2003;Lucas et al, 2005), we presently cannot rule out the possibility of a direct effect of MK-801 on serotonergic neurons of the dorsal raphe nucleus (Callado et al, 2000;Tao and Auerbach, 2000) and its blockade downstream by NBQX acting on AMPA receptors putatively located in serotonergic terminals Effect of clozapine and haloperidol X Ló pez-Gil et al (Maione et al, 1997). With regard to glutamate, however, although presynaptic AMPA receptors have been described in striatal glutamatergic axon terminals (Patel et al, 2001;Fujiyama et al, 2004), they do not seem to be present in the cortical counterparts (Fujiyama et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in line with previous reports (Moghaddam et al, 1997;Adams and Moghadam, 2001;Lorrain et al, 2003), MK-801 increases glutamate release onto AMPA/kainate receptors, which, in turn, elicit an enhanced glutamatergic output from mPFC neurons, including those projecting to the dorsal raphe nucleus, thereby increasing serotonergic cell firing and cortical 5-HT efflux. Although this functional interplay between the mPFC and the dorsal raphe nucleus is well documented (Hajós et al, 1998;Celada et al, 2001;Martín-Ruiz et al, 2001;Amargós-Bosch et al, 2003;Lucas et al, 2005), we presently cannot rule out the possibility of a direct effect of MK-801 on serotonergic neurons of the dorsal raphe nucleus (Callado et al, 2000;Tao and Auerbach, 2000) and its blockade downstream by NBQX acting on AMPA receptors putatively located in serotonergic terminals Effect of clozapine and haloperidol X Ló pez-Gil et al (Maione et al, 1997). With regard to glutamate, however, although presynaptic AMPA receptors have been described in striatal glutamatergic axon terminals (Patel et al, 2001;Fujiyama et al, 2004), they do not seem to be present in the cortical counterparts (Fujiyama et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Thus 5-HT, acting on 5-HT 1A and 5-HT 2A receptors, may finely tune the complex activity of glutamate pyramidal neurons, differently influencing various aspects of cognitive functions. It is of particular interest that mPFC neurons expressing 5-HT 1A and 5-HT 2A receptors simultaneously project to the 5-HT cells of DR nucleus and DA cells of the ventral tegmental areas (VTA) and influence their activity (Carr and Sesack, 2000;Celada et al, 2001;Hajos et al, 2003;Sesack and Bunney, 1989;Thierry et al, 1983). Cognitive functions of the prefrontal cortex are influenced by the 5-HT system (Robbins, 2000) and by an optimal level of mesocortical dopamine (DA) function (Arnsten, 1997;Granon et al, 2000;Roberts et al, 1994;Zahrt et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the mPFC not only receives 5-HT projections from the DRN, it also sends glutamatergic projections to the DRN, where they synapse on GABA interneurons (Hajos et al, 1998). Activation of the mPFC thus inhibits DRN 5-HT neurons by increasing GABAergic inhibition (Celada et al, 2001). It has been proposed that the mPFC is an important component of a 5-HT1 a receptor-mediated feedback loop (Hajos et al, 1999), and it is possible that the increases in 5-HT efflux found in the present study act to inhibit the mPFC and result in disinhibition of the DRN.…”
Section: Discussionmentioning
confidence: 99%